A stalled revolution? What can we learn from women's drop-out to part-time jobs: A comparative analysis of Germany and the UK. (December 2016) - Dieckhoff, Martina; Gash, Vanessa; Mertens, Antje; Romeu Gordo, Laura
Highlights: Power inequalities within couples predict women's drop-out from full-time work. The majority of women in partnerships earn less than 40% of household earnings. Only 5–14% of couples report equal housework contributions. Trend analysis suggests an increase in household specialization in Germany over time. Cultural context structures how couples 'do gender'. Abstract: This study examines how within-couple inequalities, that is power differences between men and women in a partnership, act as predictors of transitions from full-time to part-time employment applying Heckman corrected probit models in three different institutional and cultural contexts; Eastern Germany, Western Germany and the United Kingdom. The analyses show that when women are in a weaker position within their relationships they are more likely to drop-out of full-time work, but that this propensity varies by context. The authors also find an increased tendency over time for women to leave full-time for part-time employment in both Eastern and Western Germany, but observe no such trend in the UK. This is suggestive of ongoing incompatibilities in the institutional support for equality in dual-earning in Germany. The study uses longitudinal data covering the period 1992 until 2012 from the German Socio-Economic Panel (SOEP) for Germany and from the British Household Panel (BHPS) and the 'Understanding Society' data for the UK.